Whose side are we on? Balancing economic interests with social concerns through a service-thinking approach. Issue 1 (1st January 2021) - Cockayne, David
ABSTRACT: Research question: The aim of this study is to conceptualize sports markets in a way which enables us to (1) explore how the economic and social aspects of markets might be (re)aligned; (2) discuss practical solutions for how this might be achieved; and (3) identify what the implications are for management practice. Research methods: Literature from developments in contemporary marketing and market studies are combined to discuss the difference between interested and concerned markets. Service thinking is used ontologically and analytically to illustrate how sports organizations might reconcile the tensions and realities of existence in a business environment, and act positively within both interested and concerned market spaces. Research findings: The study suggests that sports organizations must consider the type and configuration of resource; network capabilities; and core organizational values to balance economic interests and social concerns. Secondly, practitioners should consider their organizations as a collective of co-existing entities: (1) teams; (2) clubs and (3) brands. Each organizational form has implications for the resources, capabilities and outcomes achievable by adopting service thinking. Implications: The paper provides an alternative way of thinking about sports markets, and provides a conceptual space for scholars to consider future research into the dimensions of market concern and how these shape business practice. Generic examples are presented of sports business practice that may also be useful for actors in other service industries.